Thermal degradation of biological DNA studied by dielectric spectroscopy. (December 2019) - Nizioł, Jacek; Ekiert, Robert; Kuczkowska, Justyna; Fryń, Patryk; Marzec, Monika
Abstract: Dielectric spectroscopy was tested as an alternative tool to study degradation of deoxyribonucleic acid (DNA) in its solid form. The specimens, prepared from biological DNA, were periodically heated and cooled according to a programmed scheme. Simultaneously, their dielectric parameters (permittivity and dielectric loss) were monitored as function of frequency and temperature. The analysis of Bode plots allowed to determine the upper limit of thermal stability of solid DNA at 120 °C, because heating at higher temperatures resulted in irreversible changes. These changes were identified as denaturation by gel electrophoresis and UV–vis absorption methods. Graphical abstract: Image 1 Highlights: Solid, biological DNA was compressed in tablets. Samples were studied using dielectric spectroscopy as function of temperature. Heating at temperatures less than 120°C had no effect on DNA in dielectric spectra. If heated above, dielectric characteristics of DNA changed irreversibly. This observation was identified as resulting from denaturation.